2015
DOI: 10.7567/jjap.54.030204
|View full text |Cite
|
Sign up to set email alerts
|

In situ observation of ultrasonic flip-chip bonding using high-speed camera

Abstract: Room-temperature microjoining in air ambient has been achieved by using a cone-shaped Au microbump with ultrasonic application. In situ observation of ultrasonic bonding is performed using a high-speed camera to investigate the dynamics of the bonding process. “Softening” of the bump under ultrasonic application is observed. It is suggested that bonding is achieved within 50 ms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…Besides this work, we have shown from results of in situ observation using a high-speed camera that the bump almost completely deformed at about 50 ms of the initial stage of the ultrasonic process. 19,20) These results indicate that the observed decrease in the average compressive strain is attributed to the "softening" of the bump metal under the application of ultrasonic. Softening of the metal under the application of ultrasonic was pointed out by Langenecker and others.…”
Section: Resultsmentioning
confidence: 80%
See 1 more Smart Citation
“…Besides this work, we have shown from results of in situ observation using a high-speed camera that the bump almost completely deformed at about 50 ms of the initial stage of the ultrasonic process. 19,20) These results indicate that the observed decrease in the average compressive strain is attributed to the "softening" of the bump metal under the application of ultrasonic. Softening of the metal under the application of ultrasonic was pointed out by Langenecker and others.…”
Section: Resultsmentioning
confidence: 80%
“…To further extend this technology to devices such as a mega connection image sensor, clarification of the bonding mechanism is highly demanded to shrink the pixel pitch. In our previous works, [18][19][20] we have shown that recrystallization of grains of the microbump takes place under the application of ultrasonic vibration. Figure 1(b) shows cross-sectional transmission electron microscopy (TEM) images of a bump bonded by ultrasonic bonding at room-temperature.…”
Section: Introductionmentioning
confidence: 95%
“…Numerous on-line measurements and in-situ observations of temperature [3,10,18,21], interfacial frictional force (power) [9,21,[23][24][25][26][27], frictional slip (relative motion) at the bonding interface [3,9,23,24,28], ultrasonic vibration [21,[28][29][30], deformation behavior [29,31], contact resistance [32], and electrical signals from ultrasonic generators [33] during ultrasonic bonding have been performed. The on-line measurements and in-situ observations are extremely useful and informative for comprehension of ultrasonic microjoining.…”
Section: Introductionmentioning
confidence: 99%